O uso dos contos de fadas na escola como proposta didático-metodológica para se discutir sentimentos e emoções - REIS, Gabrielle Santos (2020)
The text through a historical, social and cultural construction from childhood to achieve the best pedagogical vision of the child in the present day as subject of rights, autonomous, with desires and own opinions. With notions of construction of personality and learning in the light of Freud and Wallon, respectively, discussing the school as an integral training agent and welcoming environment. The Brazil lives murky times of retrocession, opposition to freedom of expression and censorship of a school without sex education, even though in the face of growing numbers of child abuse victims with the higher index of cases in 1 the family, searching methods to ensure that the child is protect and taught in the school. The fairy tales, increasingly frequent for diagnosis and therapy in the contemporary psychoanalytic clinic, can be used as stimulus to projections of feelings and internal conflicts, assisting in the cognitive and psychological development of the child. Realized a qualitative field research of an applied nature in which 20 children participated in a story Red Cape Tale rewrite activity to analyze the application of projection technique in children in the classroom. As a result, it was realized that the use of the story really had the expected effect with children, expressing mainly aspects of sexuality and affectivity, so it is a resource that can be used throughout the entire school year